2016
DOI: 10.1053/j.gastro.2016.08.057
|View full text |Cite
|
Sign up to set email alerts
|

An Intestinal Microbiota–Farnesoid X Receptor Axis Modulates Metabolic Disease

Abstract: The gut microbiota is associated with metabolic diseases including obesity, insulin resistance and non-alcoholic fatty liver disease (NAFLD), as demonstrated by correlative studies and by transplant of microbiota from obese humans and mice into germ-free mice. Modification of the microbiota by treatment of high-fat diet (HFD)-fed mice with tempol or antibiotics resulted in decreased adverse metabolic phenotypes. This was due to lower levels of the genera Lactobacillus and decreased bile salt hydrolase (BSH) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
199
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 282 publications
(208 citation statements)
references
References 138 publications
9
199
0
Order By: Relevance
“…Thus, modification of bacterial bile acid metabolism by use of a BSH inhibitor may represent a promising therapeutic strategy to treat type 2 diabetes–associated hyperglycemia. However, it needs to be emphasized that there are significant differences between the mechanism of metabolic disease between humans and mice and that some of the findings in the current study may not be directly translatable to humans, in particular the interaction between the intestinal microbiota, bile acid metabolites, and intestinal FXR signaling (38). Furthermore, whether activation or inhibition of intestinal FXR will be of more benefit to the treatment of metabolic disease is an area of intense interest (38,39).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, modification of bacterial bile acid metabolism by use of a BSH inhibitor may represent a promising therapeutic strategy to treat type 2 diabetes–associated hyperglycemia. However, it needs to be emphasized that there are significant differences between the mechanism of metabolic disease between humans and mice and that some of the findings in the current study may not be directly translatable to humans, in particular the interaction between the intestinal microbiota, bile acid metabolites, and intestinal FXR signaling (38). Furthermore, whether activation or inhibition of intestinal FXR will be of more benefit to the treatment of metabolic disease is an area of intense interest (38,39).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, ceramide is proposed as a common molecular intermediate linking metabolic stress to the induction of insulin resistance . Recent reports have shown that genes that increase ceramide production, including Smpd3 and Sptlc2 , have upstream FXR binding sites and were identified as direct FXR target genes in reporter gene assays . Notably, T‐βMCA, a naturally occurring FXR antagonist, was enriched in livers harvested from FGF19‐ and M70‐treated mice and could directly suppress hepatic ceramide production through FXR inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are important regulators of glucose and lipid metabolism, thermogenesis and inflammation (recent reviews [38, 39]). The bile acid derivative 6-ethylchenodeoxycholic acid (obeticholic acid) is a potent activator of FXR.…”
Section: How Does the Intestinal Microbiota Contribute To Nash?mentioning
confidence: 99%